1985
DOI: 10.1056/nejm198509263131302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Protein on the Clearance of Allopurinol and Oxypurinol

Abstract: A decrease in dietary protein is known to depress renal plasma flow and creatinine clearance. Using a randomized crossover design, we investigated the pharmacokinetics of allopurinol and its principal metabolite, oxypurinol, after oral administration of 600 mg of allopurinol in six normal subjects receiving a high-protein (268 g per day) or low-protein (19 g per day) diet. For allopurinol, the area under the curve of plasma concentration versus time increased by a factor of 1.45 (P less than 0.02), the renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…Therefore, the amino acid infusion-induced increase in the fractional clearance of oxypurinol also seems to be only attributable to increases in the plasma concentration of amino acids by the intravenous infusion of the amino acid solution. These results are compatible with the previous specula tion, suggesting that the renal transport of oxypurinol is similar to that of uric acid [18], Amino acids have been employed clinically for the treatment of several kinds of illness accompanied by hypoproteinemia, e.g., malnutri tion, chronic renal failure, or liver cirrhosis. On the other hand, allopurinol has been used for the treatment of hyperuricemia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the amino acid infusion-induced increase in the fractional clearance of oxypurinol also seems to be only attributable to increases in the plasma concentration of amino acids by the intravenous infusion of the amino acid solution. These results are compatible with the previous specula tion, suggesting that the renal transport of oxypurinol is similar to that of uric acid [18], Amino acids have been employed clinically for the treatment of several kinds of illness accompanied by hypoproteinemia, e.g., malnutri tion, chronic renal failure, or liver cirrhosis. On the other hand, allopurinol has been used for the treatment of hyperuricemia.…”
Section: Discussionsupporting
confidence: 92%
“…resulting in a decrease in the plasma concentra tion of oxypurinol. In other previous studies on the renal clearance of oxypurinol [18,19], it was demonstrated that a high-protein diet or a glucose infusion increased the uri nary excretion and the fractional clearance of oxypurinol. It was further suggested that high-protein diet-induced increases in the plasma concentrations of amino acids and/or urea or glucose infusion-induced hyperglycemia may promote the urinary excretion of oxypurinol.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, the amount of protein in the diet can influence drug metabolism and glomerular filtration. For example, in human volunteers, a protein-restricted diet resulted in a 70% decrease in the clearance of oxipurinol and uric acid (Berlinger et al, 1985).…”
Section: Introductionmentioning
confidence: 99%